PENERAPAN MODEL PEMBELAJARAN KOOPERATIF PENDEKATAN STRUKTURAL NUMBER HEAD TOGETHER (NHT) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VIII.2 SMP MUHAMMADIYAH 2 PEKANBARU - Gusti Rahman; Armis Armis; Zulkarnain Zulkarnain (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study aims to improve the learning process and improve the learning outcomes of students of class VIII.2 SMP Muhammadiyah 2 Pekanbaru odd semester of the academic year 2017/2018. Form of research conducted is action research (PTK) with 2 cycles. The subjects consisted of 16 male students and 12 female students with heterogeneous ability. Instrument of data collection in this research is observation sheet and test of mathematics learning result. The observation sheets were analyzed descriptively qualitatively, while the mathematics learning outcomes were analyzed descriptively quantitatively. From the qualitative analysis it can be seen that there is improvement of learning process from before action to cycle I and cycle II. Students are seen actively participating and becoming more independent in the learning process. The results of this study indicate the number of students who reached the KKM increased from the basic score of 3 students (10.7%) to UH I amounted to 12 people (45%) and UH 2 amounted to 18 people (64.2%). For skill assessment increased from UH I (42,5%) to UH II (64,2%) .The result of this research shows that applying cooperative learning model Structural Numbered Heads Together (NHT) approach can improve learning process and can remind learning result mathematics students of class VIII.2 SMP Muhammadiyah 2 Pekanbaru academic year 2017/2018 on the subject matter of Two-Variable Linear Equation System. Keywords: Mathematics learning outcomes, Cooperative learning, Structural Numbered Heads Together, Classroom Action Research.